V imenu natančnosti in resnice - Kristan, Silvo (Šport (Ljubljana), 2022)
I agree with the thought expressed by the author of the article that “in science... it is very difficult to lead a conversation if the fundamental concepts are not accurately defined”. I subscribe to that a hundred times over, but with a note that to be able to “lead a conversation” correctly absolute accuracy is required. It is equally difficult to “lead a conversation” if the expert discussion teems with inaccuracy, falsehood and half-truths. And there are too many examples of this in the mentioned article.
Keywords: šport; športna kultura; telesna dejavnost; telesna kultura